5-aminolevulinic acid inhibits oxidative stress and ameliorates autistic-like behaviors in prenatal valproic acid-exposed rats. (15th May 2020) - Matsuo, Kazuya; Yabuki, Yasushi; Fukunaga, Kohji
Abstract: Autism spectrum disorders (ASDs) constitute a neurodevelopmental disorder characterized by social deficits, repetitive behaviors, and learning disability. Oxidative stress and mitochondrial dysfunction are associated with ASD brain pathology. Here, we used oxidative stress in prenatal valproic acid (VPA)-exposed rats as an ASD model. After maternal VPA exposure (600 mg/kg, p.o.) on embryonic day (E) 12.5, temporal analyses of oxidative stress in the brain using an anti-4-hydroxy-2-nonenal antibody revealed that oxidative stress was increased in the hippocampus after birth. This was accompanied by aberrant enzymatic activity in the mitochondrial electron transport chain and reduced adenosine triphosphate (ATP) levels in the hippocampus. VPA-exposed rats exhibited impaired spatial reference and object recognition memory alongside impaired social behaviors and repetitive behaviors. ASD-like behaviors including learning and memory were rescued by chronic oral administration of 5-aminolevulinic acid (5-ALA; 30 mg/kg/day) and intranasal administration of oxytocin (OXT; 12 μg/kg/day), a neuropeptide that improves social behavior in ASD patients. 5-ALA but not OXT treatment ameliorated oxidative stress and mitochondrial dysfunction in the hippocampus of VPA-exposed rats. Fewer parvalbumin-positive interneurons were observed in VPA-exposed rats. Both 5-ALA and OXT treatments augmented the number of parvalbumin-positive interneurons. Collectively, our results indicate that oral 5-ALA administration ameliorated oxidative stress and mitochondrial dysfunction, suggesting that 5-ALA administration improves ASD-like neuropathology and behaviors via mechanisms different to those of OXT. Highlights: Oxidative stress and mitochondrial dysfunction underscore autism spectrum disorders. Prenatal valproic acid (VPA) exposure impaired memory and sociality later in life. Prenatal VPA exposure reduced the number of parvalbumin interneurons. These effects were rescued by 5-aminolevunilic acid (5-ALA) treatment. 5-ALA is a novel therapeutic for impaired behaviours in autism.